Problematics, Tasks and Prospects of Education Development in the Corporate Governance Area in the Russian High School - O. Yu. Kirillova (Управление)
This article discusses the problematic of educational institutions management systems in higher education. On example of the main educational program - Corporate Governance – the author shows the competencies relationship acquired during training, educational paths and work functions of professional standards underpinning training in a given subject area.